Targeting the nucleic acid oxidative damage repair enzyme MTH1: a promising therapeutic option - Ding, Yifeng; Liu, Qingquan (Frontiers in Cell and Developmental Biology, 2024)
The accumulation of reactive oxygen species (ROS) plays a pivotal role in the development of various diseases, including cancer. Elevated ROS levels cause oxidative stress, resulting in detrimental effects on organisms and enabling tumors to develop adaptive responses. Targeting these enhanced oxidative stress protection mechanisms could offer therapeutic benefits with high specificity, as normal cells exhibit lower dependency on these pathways. MTH1 (mutT homolog 1), a homolog of Escherichia coli’s MutT, is crucial in this context. It sanitizes the nucleotide pool, preventing incorporation of oxidized nucleotides, thus safeguarding DNA integrity. This study explores MTH1’s potential as a therapeutic target, particularly in cancer treatment, providing insights into its structure, function, and role in disease progression.